The Structural Basis of Babesia orientalis Lactate Dehydrogenase - Yu, Long; Liu, Qin; Luo, Wanxin; Zhao, Junlong; Alzan, Heba F.; He, Lan (Frontiers in Cellular and Infection Microbiology, 2022)
The glycolytic enzymes play a crucial role in the anaerobic glycolysis of apicomplexan parasites for energy generation, consequently it consider as potential targets for new drugs development. Available studies revealed that lactate dehydrogenase (LDH), a glycolytic enzyme, is a potential drug target in Plasmodium, Toxoplasma, Cryptosporidium and Piroplasm. Herein, Babesia orientalis (Bo) LDH was used as a model to reveal the structural basis of LDH in Babesia spp., we solved the crystal structure of apo BoLDH at 2.67 Å resolution in the space group P1. A five peptide insertion appears in the active pocket loop of BoLDH to create a larger catalytic pocket, like other protozoa (except for Babesia microit LDH) and unlike its mammalian counterparts, and the absence of this extra insertion inactivates BoLDH. Without ligands the apo BoLDH takes R-state (relaxed) with active-site loop open, the feature is obviously different from that of allosteric LDHs in T-state (tense) with active-site loop open. Compared with allosteric LDHs the extra salt bridges and hydrogen bonds make the subunit interfaces of BoLDH more stabilization, and result in the absence of T-state. Interestingly, BoLDH exhibits the ability to adapt quickly to the synthetic co-factor APAD+ and shows a ~3-fold higher Kcat value than NAD+. In addition, the enzymatic activity of BoLDH was inhibited non-competitively by polyphenolic gossypol with a Ki value of 4.25 μM, BoLDH is sensitive to inhibition of gossypol and possibly to new derivatives of the compound. The current work provides the structural basis of BoLDH for the first time, and suggests further investigation on the structure of Babesia spp. LDH which indeed would facilitate the screening and designing of new LDH inhibitors for controlling the intracellular proliferation of Babesia spp.